Diagnostic Performance of Seven Commercial COVID-19 Serology Tests Available in South America - Rivera-Olivero, Ismar A.; Henríquez-Trujillo, Aquiles R.; Kyriakidis, Nikolaos C.; Ortiz-Prado, Esteban; Laglaguano, Juan Carlos; Vallejo-Janeta, Alexander Paolo; Lozada, Tannya; Garcia-Bereguiain, Miguel Angel, UDLA COVID-19 team (Frontiers in Cellular and Infection Microbiology, 2022)
Background Although RT-qPCR remains the gold-standard for COVID-19 diagnosis, anti-SARS-CoV-2 serology-based assays have been widely used during 2020 as an alternative for individual and mass testing, and are currently used for seroprevalence studies. Objective To study the clinical performance of seven commercial serological tests for COVID-19 diagnosis available in South America. Methods We conducted a blind evaluation of five lateral-flow immunoassays (LFIA) and two enzyme-linked immunosorbent assays (ELISAs) for detecting anti-SARS-CoV-2 antibodies. Results We found no statistically significant differences among ELISA kits and LFIAs for anti-SARS-CoV-2 IgG sensitivity (values ranging from 76.4% to 83.5%) and specificity (100% for the seven serological assays). For anti-SARS-CoV-2 IgM, the five LFIAs have a significantly higher sensitivity for samples collected 15 days after the first time RT-qPCR positive test, with values ranging from 47.1% to 88.2%; moreover, the specificity varied from 85% to 100%, but the only LFIA brand with a 100% specificity had the lowest sensitivity. Conclusion The diagnostic performance of the seven serological tests was acceptable for the seven brands tested for anti-SARS-CoV-2 IgG detection for seroprevalence screening purposes. On the other hand, our results show the lack of accuracy of anti-SARS-CoV-2 IgM detection in LFIAs as a tool for SARS-CoV-2 acute-phase infection diagnosis.